Ответы и объяснения

2014-02-27T14:33:36+04:00
Выражение: (6*x-x^2)^2-x^2*(x-1)*(x+1)+6*x*(3+2*x^2)
Решаем по шагам:
1. 36*x^2-12*x^3+x^4-x^2*(x-1)*(x+1)+6*x*(3+2*x^2)
2. 36*x^2-12*x^3+x^4-(x^3-x^2)*(x+1)+6*x*(3+2*x^2)
3. 36*x^2-12*x^3+x^4-(x^4-x^2)+6*x*(3+2*x^2)
4. 36*x^2-12*x^3+x^4-x^4+x^2+6*x*(3+2*x^2)
5. 36*x^2-12*x^3+x^2+6*x*(3+2*x^2)
6. 37*x^2-12*x^3+6*x*(3+2*x^2)
7. 37*x^2-12*x^3+(18+12*x^2)*x
8. 37*x^2-12*x^3+18*x+12*x^3
9. 37*x^2+18*x
Ответ: 37*x^2+18*x
2014-02-27T14:46:20+04:00
(6x-x^2)^2-x^2(x-1)(x+1)+6x(3+2x^2)=36x^2-x^4-x^2(x^2+x-x-1)+18x+12x^3= 36x^2-x^4-x^4-x^3+x^3+x^2+18x+12x^3=37x^2-2x^4+12x^3+18x = можно еще вынести х за скобки =x(37x-2x^3+12x^2+18)